Growth and characteristics of islands and quantum dots of germanium and indium gallium arsenide /lcAmira Saryati Ameruddin - 541108 Amira Saryati Ameruddin,ld1985-; Zulkafli Othaman,lcsupervisor; Fakulti Sains
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010